När streetsmart banar tricksterns väg till makten... - Österlund-Pötzsch, Susanne (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2020)
The label street-smart is a customary way to describe a person who manages to get by despite adversities. The concept highlights an innate quality in a person, characterized by slyness, resourcefulness and wittiness among other things. However, street-smart can also refer to knowledge a person has acquired through experience. Street-smart is practical rather than theoretical knowledge. The figure of the trickster is street-smart incarnate. These liminal characters appear worldwide in mythology, folklore and popular culture but also as real life individuals. One of the tricksters’ many guises is the "shrewd political leader" – a role that is increasingly common of late. The trickster politician thrives in times of uncertainty, unrest and liminality. They often profile themselves as "selfmade" and as representing the "popular voice", while they excel in shunning responsibility and shifting blame. The question that emerges is what happens when the boundary transgressing, marginal trickster becomes the norm-maker and the centre of power.